2011
DOI: 10.1021/jp202130g
|View full text |Cite
|
Sign up to set email alerts
|

TiN Decoration of Single-Wall Carbon Nanotubes and Graphene by Density Functional Theory Computations

Abstract: Ti nanostructures on Single-Wall Carbon Nanotubes (SWCNTs) have attracted considerable attention due to their potential applications in electronic nanodevices and molecular adsorption. We report on Density Functional Theory (DFT) results referring to Ti N (N = 1, 2, 3, 7, 13) supported on SWCNTs and graphene. Two new equivalent positions emerged that trisect the line joining the hexagon normal to the tube’s axis sides (TSH). These sites accommodate the dimers and trimers in compact linear and 2D triangular fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The binding energy of the graphene and neutral rutile (1 1 0) surface is only 0.514 eV, and this binding energy is so weak that it hardly changes geometrical structure of graphene. And two types CÀC bond length (1.41 Å and 1.44 Å) are found in graphene/ rutile (1 1 0) composites, corresponding to the values found in previous reports [28,29]. The work function of three composite systems are estimated, and the theoretical values are 4.06 (neutral), 3.45 (negatively-charged), and 3.25 eV (oxygen-deficient), respectively.…”
Section: Mode Building Of Graphene/rutile (1 1 0) Compositessupporting
confidence: 79%
“…The binding energy of the graphene and neutral rutile (1 1 0) surface is only 0.514 eV, and this binding energy is so weak that it hardly changes geometrical structure of graphene. And two types CÀC bond length (1.41 Å and 1.44 Å) are found in graphene/ rutile (1 1 0) composites, corresponding to the values found in previous reports [28,29]. The work function of three composite systems are estimated, and the theoretical values are 4.06 (neutral), 3.45 (negatively-charged), and 3.25 eV (oxygen-deficient), respectively.…”
Section: Mode Building Of Graphene/rutile (1 1 0) Compositessupporting
confidence: 79%
“…491 In this case, it was also shown that the charge transfer is enhanced for doublewalled CNT compared to single-walled CNT. Similar charge transfers from the metal to the carbon support were reported for Mn 7 /G, 142 Ti 13 /G, 513 and Fe 1−5 /G. 514 As expected, the metal atoms in the interfacial layer have much more positive/ negative charges (according to the direction of the charge transfer) than those in the upper layer, as shown on Figure 26 for Pt 37 and Ru 13 clusters.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…As a result, enough nucleation sites for subsequent ALD reaction are provided to cover the entire nanotube. Some theoretical calculations show strong interaction between titanium and carbon, resulting in covalent bond formation between Ti and CNTs or graphene [36,37,38], which contradicts the idea of minimizing interaction between nanotubes and coatings. However, according to Density Functional Theory calculations, Ti is very reactive with O 2 and oxidizes rapidly in its presence, significantly weakening Ti–C interaction upon oxidation [39,40].…”
Section: Resultsmentioning
confidence: 99%